"Register and Roll": A Novel Initiative to Improve First Door-to-Balloon Time in ST Elevation Myocardial Infarction. (8th October 2012) - Amruthlal Jain, Sachin Kumar; Ismail, Yousif; Shaw, Michael; David, Shukri; Alexander, Patrick
Abstract : Objective . We examined the cause of transfer delay in patients with an acute ST-segment myocardial infarction (STEMI) from non percutaneous coronary intervention (PCI) capable to PCI capable hospitals. We then implemented a novel, simple, and reliable initiative to improve the transfer process. Background . Guidelines established by the ACC/AHA call for door-to-balloon times of ≤90 minutes for patients with STEMI. When hospital transfer is necessary, this is only met in 8.6% of cases. Methods . All patients presenting with STEMI to a non-PCI capable hospital from April 2006 to February 2009 were analyzed retrospectively. After identifying causes of transfer delay the "Register and Roll" initiative was developed. An analysis of effect was conducted from March 2009 to July 2011. Results . 144 patients were included, 74 pre-initiative and 70 post- initiative. Time to EMS activation was a major delay in patient transfer. After implementation, the EMS activation time has significantly decreased and time to reperfusion approaches recommended goal (Median 114 min versus 90 min, P < 0.001 ), with 55% in <90 minutes. Conclusion . "Register and Roll" streamlines the triage process and improves hospital transfer times. This initiative is easily instituted and reliable in a community hospital setting where resources are limited.